The photography ideas book : inspiration and tips taken from over 80 photos - Yabsley, Lorna (London : Ilex Press, 2019)
It's time to refresh your creativity with a lively exploration of photography at the cutting edge. There's always a new angle with which to shoot your subject, a different light to capture, or a completely new genre to try out, so there's never an excuse for your camera, whatever kind it is, to gather dust! This little book, full of big ideas from a range of iconic and contemporary photographers, will inspire you to think differently. With a new concept on every page, you will discover fresh ways of tackling your subjects to create work that is original and exciting.
Keywords: Photography -- Technique; Photography, Artistic